Association between pre-stroke sarcopenia risk and stroke-associated infection in older people with acute ischemic stroke - Song, Xiaodong; Chen, Xufeng; Bai, Jie; Zhang, Jun (Frontiers in Medicine, 2023)
Background: Stroke-associated infection (SAI) is a common complication after stroke. The incidence of infection was higher in people with sarcopenia than in the general population. However, the relationship between pre-stroke sarcopenia risk and SAI in older patients has not been confirmed. This study aimed to investigate the association between pre-stroke sarcopenia risk and SAI in older patients with acute ischemic stroke (AIS). Methods: This retrospective study was conducted by Peking University People's Hospital. We evaluated the pre-stroke sarcopenia risk by applying the SARC-F questionnaire. Multivariate logistic regression was applied to explore the association between pre-stroke sarcopenia risk and SAI. Results: A total of 1002 elder patients with AIS (592 male; 72.9 ±8.6 years ) were enrolled in our study. Pre-stroke sarcopenia risk was found in 29.1% of the cohort. The proportion of patients with pre-stroke sarcopenia risk was larger in the SAI group than in the non-SAI group (43.2% vs. 25.3%, p < 0.001). In multivariate logistic analysis, pre-stroke sarcopenia risk was shown to be independently associated with SAI (OR = 1.454, 95% CI: 1.008-2.097, P = 0.045) after adjusting for potential factors. This association remained consistent across subgroups based on age, sex, body mass index, smoking status, drinking status, diabetes, hypertension, and dyslipidemia. Conclusion: Pre-stroke sarcopenia risk was independently associated with SAI in older patients with AIS. Our findings highlight the significance of pre-stroke sarcopenia identification in the prevention and management of SAI in this population.